Microbial communities of polluted sub-surface marine sediments. (June 2018) - Catania, Valentina; Cappello, Simone; Di Giorgi, Vincenzo; Santisi, Santina; Di Maria, Roberta; Mazzola, Antonio; Vizzini, Salvatrice; Quatrini, Paola
Abstract: Microbial communities of coastal marine sediment play a key role in degradation of petroleum contaminants. Here the bacterial and archaeal communities of sub-surface sediments (5–10 cm) of the chronically polluted Priolo Bay (eastern coast of Sicily, Italy), contaminated mainly by n-alkanes and biodegraded/weathered oils, were characterized by cultural and molecular approaches. 16S-PCR-DGGE analysis at six stations, revealed that bacterial communities are highly divergent and display lower phylogenetic diversity than the surface sediment; sub-surface communities respond to oil supplementation in microcosms with a significant reduction in biodiversity and a shift in composition; they retain high biodegradation capacities and host hydrocarbon (HC) degraders that were isolated and identified. HC-degrading Alfa, Gamma and Epsilon proteobacteria together with Clostridia and Archaea are a common feature of sub-surface communities. These assemblages show similarities with that of subsurface petroleum reservoirs also characterized by the presence of biodegraded and weathered oils where anaerobic or microaerophilic syntrophic HC metabolism has been proposed. Highlights: A microbiological survey of chronically polluted sub-surface marine sediments (sss, 5–10 cm) is presented. Sss are contaminated mainly by n-alkanes and biodegraded/weathered oils. Sss microbial communities display lower diversity than surface sediment and retain biodegradation capacities. Sss communities share common features with that of ss petroleum reservoirs.